Force and motion coordination of legged robots for walking ability improvement - Zhou, Debao. (2008)
Compared with a wheeled mobile robot, a legged robot is more capable to walk in un-structured natural environment. To fully exert this ability in such a condition is one of the main concerns in the development of legged robots. It is well-known that the interaction between the foot and the ground plays a crucial effect on the walking ability. Considering leg-end forces, three methods are proposed in this thesis to improve the walking ability of a legged robot.